Microbiological characteristics of marketed rohu (Labeo rohita) - Sinha, D K; Choudhary, S P; Narayan, K G (Indian Journal of Fisheries, 2011)
Consumption of fish and fish products is not always safe. At times, these contain microorganisms of public health significance, viz. Escherichia coli (Saxena et al. 1987), Staphylococcus (Sanjeev et al. 1985), Clostridium perfringtns. Salmonella and others (Shewan 1962, Annymous 1974). The present investigation rep arts the microbial flora of marketed rohu.